Topological strings on compact Calabi-Yau's - Hollands, L (2007)
Some steps towards solving topological string amplitudes on Calabi-Yau spaces have been taken lately: all-genus amplitudes have been computed for non-compact toric Calabi-Yau threefolds, local Riemann surfaces and K3-fibrations, while progression has been made for the Fermat quintic threefold. However, the building blocks of all-genus topological string amplitudes for general compact Calabi-Yau's remain unknown. We study some aspects of the underlying geometry and discuss difficulties. © 2007 Elsevier B.V. All rights reserved.